Palimpsestos: Ana Miranda y la lectura de la historia literarria brasileña - Esteves, Antonio Roberto [UNESP] (My University, 2011)
We can notice in Brazilian literature —both past and contemporary— the presence of the historical novel in its several modalities which include traditional models but also contemporary formulations that break old models with irreverence. Among them are the historiographical metafictions (Hutcheon, 1991), which propose the rereading not only of history but also of literature itself. Therefore, in the large number of historical characters which are fictionalized by contemporary Brazilian historical novel in the last decades, this essay intends to discuss how Ana Miranda engages in reading the history of Brazilian literature through fiction in three of her novels. The first is Boca do inferno (1989), whose protagonists are two of the main representatives of Brazilian colonial barroque, Father Antônio Vieira and poet Gregório de Matos. Following the chronological order of protagonist writers, the next novel to be discussed is Dias & dias (2002), whose action is centered in Gonçalves Dias, a well known poet of national Romanticism. The third is A última quimera (1995), which makes an outline of Brazilian literature at the beginning of the 20th century, dealing with Augusto dos Anjos and Olavo Bilac. By inverting some traditional viewpoints, Ana Miranda proposes, as in a palimpsest, the rereading and discussion of the national literary cânon and its construction.

Se puede observar en la Literatura Brasileña, tanto la del pasado, como la contemporánea, la presencia de la novela histórica en sus diversos tipos de registro, que abarcan modelos tradicionales, pero también formulaciones más actuales, que rompen, irreverentes, los antiguos modelos. Entre ellas, están las metaficciones historiográficas (Hutcheon, 1991), que, además de la Historia, se plantean releer la propia Literatura. Así, en la vasta galería de personajes históricos ficcionalizados en estas novelas de las últimas décadas, los actores son los mismos escritores. En ese contexto, el presente trabajo pretende señalar cómo Ana Miranda se propone leer la historia de la Literatura Brasileña a través de la ficción, en tres de sus novelas. La primera es Boca do inferno (1989), cuyos protagonistas son dos de los principales representantes del Barroco Colonial Brasileño, el padre Antônio Vieira y el poeta Gregório de Matos. En orden cronológico de los escritores protagonistas, la siguiente novela para ser analizada es Dias & dias (2002), cuya acción se centra en Gonçalves Dias, conocido poeta del Romanticismo nacional. La tercera es A última quimera (1995), que insinúa un panorama de las letras brasileñas, en los primeros años del siglo xx, al tratar sobre los poetas Augusto dos Anjos y Olavo Bilac. Invirtiendo algunos puntos de vista tradicionales, Ana Miranda presenta, como en un palimpsesto, la relectura y la discusión del canon literario nacional y su construcción.
Keywords: Contemporary Brazilian historical novel; Rereading of literary cânon; Ana Miranda (1951); Historiographical metafiction; Intertextualities; Women’s novel; Novela histórica brasileña contemporánea; Relecturas del canon literario; Ana Miranda (1951); Metaficción historiográfica; Intertextualidades; Narrativa de autoría femenina